Association of Neutrophil to Lymphocyte Ratio With Pulmonary Function in a 30-Year Longitudinal Study of US Veterans - Gao, X.; Coull, B.; X. Lin; Vokonas, P.; Sparrow, D.; Hou, L.; DeMeo, D. L.; Litonjua, A. A.; Schwartz, J.; Baccarelli, A. A. (JAMA Netw Open, 2020)
Importance: Chronic obstructive pulmonary disease (COPD) is a critical public health burden. The neutrophil to lymphocyte ratio (NLR), an inflammation biomarker, has been associated with COPD morbidity and mortality; however, its associations with lung function decline and COPD development are poorly understood. Objective: To explore the associations of NLR with lung function decline and COPD risks. Design, Setting, and Participants: This longitudinal cohort study included white male veterans in the US with more than 30 years of follow-up to investigate the associations of NLR with lung function, COPD, and hypomethylation of cg05575921, the top DNA methylation marker of lung function changes in response to tobacco smoking. This study included 7466 visits from 1549 participants, each examined up to 13 times between 1982 and 2018. A subgroup of 1411 participants without COPD at baseline were selected to analyze the association of NLR with incident COPD. Data were analyzed from September 2019 to January 2020. Exposures: The primary exposure was NLR, which was estimated using automated whole blood cell counts based on a blood sample collected at each visit. The methylation level of cg05575921 was measured in blood DNA from a subgroup of 1228 visits. Main Outcomes and Measures: The outcomes of interest were lung function, measured as forced respiratory volume in the first second (FEV1) in liters, forced vital capacity (FVC) in liters, percentage of FVC exhaled in the first second (FEV1/FVC), and maximal midexpiratory flow rate (MMEF) in liters per minute and COPD status, defined as meeting the Global Initiative for Chronic Obstructive Lung Diseases stage II (or higher) criteria. Both outcomes were measured as each visit. Results: Among 1549 included men (mean [SD] age, 68.3 [9.3] years) with 7466 visits from 1982 to 2018, a 1-unit increase in NLR was associated with statistically significant mean (SE) decreases of 0.021 (0.004) L in FEV1, 0.016 (0.005) L in FVC, 0.290% (0.005) L in FVC, 0.290% (0.065%) in FEV1/FVC, and 3.65 (0.916) L/min MMEF. Changes in NLR up to approximately 10 years were associated with corresponding longitudinal changes in lung function. Furthermore, this increase in NLR was associated with 9% higher odds of COPD (odds ratio, 1.09 [95% CI, 1.03-1.15]) for all visits and 27% higher risk of incident COPD (odds ratio, 1.07 [95% CI, 1.07-1.51]) for participants without COPD at baseline. Additionally, a 1-unit increase in NLR was associated with a mean (SE) decrease of 0.0048 (0.0021 in cg05575921 hypomethylation, which may mediate the adverse association of NLR-related inflammation on lung function. Conclusions and Relevance: These findings suggest that NLR may be a clinically relevant biomarker associated with high risk of lung function impairment and COPD alone or in combination with DNA methylation profiles.
Keywords: Aged Biomarkers DNA Methylation Forced Expiratory Volume Humans *Leukocyte Count Longitudinal Studies Lung/*physiopathology *Lymphocyte Count Male Maximal Midexpiratory Flow Rate *Neutrophils/pathology Pulmonary Disease; Chronic Obstructive/diagnosis/pathology Respiratory Function Tests/statistics & numerical data Risk Factors United States/epidemiology Veterans/*statistics & numerical data Vital Capacity